Analysis Of The Principles Of Transparency, Participation, Accountability Dan Value For Money In Public Policy Formulation - et. al., Iyoyo Dianto, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This Study Is New And Different From Previous Studies. This Research Is A Comprehensive Assessment Of The Implementation Of The Principles In Public Policy Formulation Based On The Theory, Regulations And In Indonesia. There Are Several Phenomena And Dynamics Related To The Implementation Of Principles In The Public Policy Formulation Process, Especially In Developing Countries. This Study Aims To Comprehensively Analyze The Effect Of The Implementation Of The Principles Of Transparency, Participation, Accountability And Value For Money In Public Policy Formulation In Indonesia, Especially In Riau Province.